Art 1960 The Use Of Identity Politics In Eectoral Campaigns In Indonesia A Perspektive Of Electoral Law And Islamic Law - MOH. ALI FIKRI; Sahran Raden; Mohamad Oktafian (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
The increasing use of identity politics in electoral campaigns in Indonesia has become a significant issue in contemporary democratic practices, particularly due to its potential to trigger social polarization and undermine democratic quality. This study aims to analyze the forms and patterns of identity politics in campaigns, examine them from the perspectives of Indonesian electoral law and Islamic law, and conduct a comparative analysis between the two legal systems. This research employs a normative legal method with a qualitative approach, utilizing statutory, conceptual, and comparative approaches. Data were collected through library research and analyzed using descriptive qualitative analysis. The findings indicate that identity politics manifests in religious, ethnic, and social group narratives, with patterns ranging from affirmative to exclusive and provocative forms. From the perspective of Indonesian electoral law, such practices are restricted due to their potential to incite conflict and violate legal norms. Meanwhile, Islamic law also prohibits divisive identity-based practices as they contradict principles of unity, justice, and public welfare. The comparative analysis reveals that both legal systems share similar normative values in rejecting harmful identity politics, although they differ in their sources and enforcement mechanisms. This study concludes that integrating legal and ethical approaches is essential to promote inclusive, ethical, and high-quality democratic practices.